Translating the Jump of a Horse – two translations of Federico García Lorca’s Poeta en Nueva York - Holm, Nanna (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This article deals with metaphor translation emphasising the common ground between translation theory and Cognitive Linguistics (CL). Within the framework of CL, a comparative study of two Danish translations of Spanish poet Federico García Lorca ’s ‘Poeta en Nueva York’ is presented, focusing on a selection of metaphors that form networks throughout the work in question. It is then analysed if and how these metaphoric networks have been successfully transferred into the target language (TL). In conclusion, some remarks are made on the contribution of CL to the overall discussion of the translatability of metaphors.